Polarisasi Politik dengan Partisipasi Politik Mahasiswa di Media Sosial: Systematic Literature Review - Citra Rahma Deya; Cindy Claudia; Raudhahtul Jannah; Muhammad Al Zikra; Aflah Zakinov Irta (CV. ITTC INDONESIA, 2026)
Social media has emerged as a new arena for political communication, particularly among the younger generation, including teenagers and university students. In the context of the 2024 General Election, platforms such as TikTok and Instagram play a pivotal role in fostering political participation, shaping public opinion, and reinforcing the political identities of young people. This study aims to examine the impact of social media on political participation and the potential for polarization it creates. A literature review method was employed, analyzing research findings from scholarly journals published between 2019 and 2024. The results indicate that social media can enhance political engagement through easy access to information, online discussions, and the appeal of visual content. However, social media usage can also lead to opinion polarization driven by platform algorithms, the spread of misinformation, and the influence of public figures. In conclusion, social media plays a dual role in democracy: serving as a vehicle for political empowerment while also acting as a potential source of disinformation. Therefore, enhancing digital literacy among users is crucial to fostering a healthy and inclusive democratic environment.